Pengembangan Bahan Ajar PAI Berbasis Holistik Integratif dalam Membentuk Karakter Religius Anak Usia Dini di RA Ulul Albab Batujajar Kabupaten Bandung Barat - Lala NurbaetiFajri; Ikes Rostina; Millati Fitri Amaliya; Anie Rohaeni (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
Islamic Religious Education (IRE) in early childhood education plays a strategic role in establishing religious character as the foundation for children's holistic development. However, the teaching materials commonly used in Raudhatul Athfal institutions remain focused on delivering religious knowledge and have not fully accommodated the comprehensive developmental needs of young learners. This study aims to describe the development of Holistic-Integrative Islamic Religious Education teaching materials to foster religious character among early childhood learners at RA Ulul Albab Batujajar, West Bandung Regency. The study employed a descriptive qualitative approach, with data collected through observations, interviews, documentation, and literature review. Data were analyzed using data reduction, data display, and conclusion drawing, while source triangulation was applied to ensure trustworthiness. The findings indicate that Holistic-Integrative teaching materials effectively integrate spiritual, socio-emotional, cognitive, language, physical-motor, and family involvement aspects into the learning process. The implementation includes educational games, worship habituation, Islamic storytelling, simple projects, and collaborative activities involving teachers and parents. These learning experiences are meaningful, contextual, and developmentally appropriate for early childhood learners, contributing to the formation of religious character, including discipline in worship, honesty, responsibility, social empathy, and devotion to Allah. The study is expected to provide a practical and theoretical reference for developing innovative, child-centered, and humanistic Islamic Religious Education teaching materials aligned with the implementation of the Merdeka Curriculum in early childhood education.